Electronic transitions in single and double quantum wells made of III–V compound semiconductors (Superficies y Vacío, 2013)
In this work, we calculate the electronic inter-band transitions in low dimensional nanostructures employing the effective mass approximation. With the help of the well-known models of square quantum well (SQW) and the symmetric square double quantum well (DQW), we calculate the energy levels in nanostructures commonly grown by molecular beam epitaxy (MBE) of III–V compound semiconductors. We choose in our calculations quantum wells (QWs) made of heterostructures without strain such as GaAs/AlxGa1-xAs, as well as heterostructures where the strain is very important such as InxGa1-xAs/GaAs and InAs/GaAs. We present our results showing the electronic transition energy versus the well width in the SQW case, or versus the middle barrier width in the DQW case. A discussion about the wave functions in the SQW and its coupling in the DQW is included.